Fenomenologia e a(s) geografia(s) da educação à distância: experiências do espaço universitário por acadêmicas/os em formação EaD - Nunes, Leonardo Berté (2023)
This research deals with what we call the “university space”, that is, a space formed through experiences, perceptions and representations in higher education institutions. Such a “university space” is shaped through the formative process such as teaching, research and extension activities, but also through student housing in public universities or even the various sociabilities that permeate this moment of these subjects” existence. However, the direction of the present research concerns this university space for those students of Distance Education (DE), that is, a university space that has cyberspace as specific mediation through platforms and virtual learning environments, as well as other forms of cyberspace, such as social networks. For this, we use phenomenology to discuss questions about experience, perception and representation in order to understand how subjects, when experiencing the world, represent it, giving it certain explanations that give meaning to these experiences. This discussion was carried out by authors such as Merleau- Ponty (2018), Serpa (2019), Gil Filho (2005), among others, who allow tracing the imbrication between experiences and perceptions with the representations that constitute everyday life. Therefore, in order to operationalize the research, we used what we call “geographical narratives”, that is, a research strategy specific to this research that allows us to present the researcher”s encounter with the participants that constitute the studied phenomenon. That is, this strategy makes it possible to find out not only what the students of the modality who were willing to participate in the research tell us, but this encounter between the researcher and them. From this, we traced the process of phenomenological reduction in two steps that led us to understand the constituent experiences of the “university space” of distance education. This, in turn, is shaped in the students” perceptions when they connect to platforms and other forms of communication with their courses in the most diverse ways and conforms from representations that revolve around the discussion of the quality of distance education in different aspects.